Use of Concept Mapping to Identify Expectations of Pharmacy Students Selecting Elective Courses - Ruth Vinall; Peter Balan (MDPI AG, 2021)
The objective of this study was to demonstrate the use of concept mapping as a method for analyzing pharmacy students' qualitative perceptions of their expectations of elective courses and to thus help guide delivery methods and course content. A survey containing demographic, Likert scale, and open-ended questions was administered to second-year pharmacy students prior to the start of elective courses and an innovative methodology, concept mapping, was used to identify major themes relating to student expectations. The association between preferred class delivery method (online versus in person) with student gender and English-as-a-second-language status (ESL) was also assessed. Note that this study was conducted prior to the COVID-19 pandemic. Ninety-eight out of 133 students (74%) completed the survey. Overall, 56% students stated that they preferred online delivery of courses (68% of these students were female, 36% were male). ESL status did not impact preference. The most common themes relating to student course expectations were the desire to learn about the elective course topic as well "real-world" utility. Our combined data indicate that delivery method is a key factor contributing to students' choice of elective course and that concept mapping is an effective and efficient way to help identify student expectations of elective courses.